(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The expansion of EU concerning ten more countries (1st of May, 2004) meaningly influenced its size and character. The membership of EU meant, for all „newcomer countries”, necessity of new political, structural and legal standards implementation. The importance of local authorities grew enormously because the process of union law implementation was local governments’ responsibility. Many tasks given to local au-thorities would not be possible to fulfill if it was not for eventuality to use union money. Polish local authorities have become the greatest beneficiary of structural funds re-sources and, as it is widely known, the possibility to dispose great amounts of money brings real power.